Innovation and Competitive Advantage in the Selected Manufacturing Firms in the South-East, Nigeria - Nnenne Adani (Trescode Green Organization, 2025)
The study examined the extent to which innovation influence competitive advantage in the selected manufacturing firms in the South-East, Nigeria. This study adopted descriptive survey research design. The target population in this study was two thousand and two (2002) staff in the selected manufacturing firms in Southeast, Nigeria. Random sampling was used to obtain a sample size of 322 respondents. Primary data were collected with the use of structured questionnaire. Pearson Product-moment Correlation was used to test the hypothesis, which revealed that: innovation exerts a moderate statistical influence on competitive advantage in selected manufacturing firms in Southeast, Nigeria (r = 0.61, p < .01). In conclusion, innovative firms are likely to enjoy competitive advantage more than those who maintain old ways of doing business. The study recommends that manufacturing firms should continuously review and improve their product offerings by introducing innovative features and attributes that set them apart in the industry.